Pomological and sensory properties of 8 different fig varieties in Croatia - Prgomet, Iva (Array, 2021)
The common fig (Ficus carica L.) is a fruit species traditionally cultivated in coastal Croatia. After some years of being of low commercial value, the interest in fig consumption and cultivation in this region seems to start following the increasing trend. One way of promoting fig consumption is to identify the varietal sensory properties, intending to match the consumer preferences. For this reason, the goal of this study was to evaluate sensory properties and pomological characteristics of fresh fruits of five dark ("Šaraguja", "Miljska", "Crnica", "Piombinese", "Nero Rosso") and three light-coloured ("Petrovača bijela", "Tiger", "San Martino") skin fig varieties, grown in Croatia. Figs were harvested from 5-years old trees in the fig experimental orchard located in Istria County (Croatia). Significant differences were observed for the properties of appearance, odour, flavour, and taste. Fresh fruits of varieties 'Šaraguja' and 'Tiger' reached the highest scores for the intensity of taste, fig odour, and flavour, compared to all the others. The highest values regarding fruit thickness and width were recorded from the variety 'Petrovača bijela', lenght from the variety 'Šaraguja', while 'San Martino' variety had the fruits of biggest weight. The variety 'Miljska' displayed the lowest values in all the observed pomological parameters. The importance of the pomological description and observation of sensory parameters of fresh figs lies in permitting the producers to decide the potential of each variety based on consumer preferences.